Vibrational Entropy Contribution to Mixing Free Energy of Ni-Rich LiNi1-yCoyO2. Issue 6 (1st June 2022) - Benedek, Roy
Abstract : First principles density-functional-theory calculations are performed of the mixing free energy of the layered oxide LiNi1− y Co y O2, a model Li-ion-battery cathode material, at 1000 K. Analysis of internal energy, LN exchange, configurational entropy and vibrational entropy are combined to obtain the net mixing free energy. The vibrational entropy requires a more indirect treatment than the other terms; analysis based on heat capacity is presented to show that the vibrational entropy is of comparable magnitude to the configurational entropy, and it tends to promote solid-solution behavior in LiNi1− y Co y O2 .